How to you find the general solution of 4yy'−3e^x=0?

abkapseln87 2022-09-29 Answered
How to you find the general solution of 4 y y - 3 e x = 0 ?
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Leslie Braun
Answered 2022-09-30 Author has 7 answers
Changing the notation from Lagrange's notation to Leibniz's notation we have:

4 y d y d x - 3 e x = 0
4 y d y d x = 3 e x

This is a First Order sepaable DE, and "seperating the variables" give is

4 y d y = 3 e x d x

Integrating gives us:

2 y 2 = 3 e x + C 1
y 2 = 3 2 e x + C (by writing C 1 = 1 2 C )
y = 3 2 e x + C
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions